The effectiveness of two-versus three-start helical strakes in suppressing VIV of flexible cylinder - Lee, Kee Quen (2014)
The proposed paper investigates experimentally the effectiveness of strakes in suppressing the vortex-induced vibration (VIV) of a long flexible cylinder by varying the number of helix of the strakes, which differ from the previous studies that only focus on short rigid cylinder. The experiment was conducted in the towing tank with constant velocity under subcritical Reynolds number (0.14x104 - 1.37x104) by using a poly vinyl chloride cylinder with aspect ratio of 162. CCD cameras were installed to capture the amplitude vibration while the variation of tension was measured by using tension load-cell. The drag force coefficient and the cross-flow and in-line frequency response were obtained from the strain gauges. The purpose of the present study is to identify the main deficiency and advantage of a two-start helical strakes compare to a three-start helical strakes in reducing the VIV of a low mass ratio flexible riser. The experimental result shows that the two-start helical strakes perform well in mitigating the VIV in low reduced velocity range. However, its effectiveness in suppressing the vibration amplitude of flexible cylinder is far smaller than the three-start helical strakes. Substantial amplitude mitigation is found for the three-start helical strakes, but with significant amplification of drag at high reduced velocity, which is unfavourable. On the other hand, although the mean drag coefficient is slightly higher for the two-start helical strakes in the lock-in region, the drag force response is more consistent and independent to the velocity changes at high reduced velocity.